Digitalisasi Pencatatan Laporan Keuangan pada UMKM Surya Mobil - Candy Candy; Kelvin Kelvin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Surya Mobil is an MSME in the service and automotive sector in Batam City that was established in 2000. MSMEs experience problems related to inefficient manual financial recording, recording errors, and inaccurate data. The main objective of the service is to help digitize MSME financial recordings with spreadsheets. Data collection is carried out using the interview method with the owner, as well as observation and documentation of the location and operational activities of Surya Mobil. Activities produce general, purchase, and sales journals for data entry. In addition, there are automated ledgers and financial reports that can be accessed in real-time. The post-implementation impact received positive feedback from the owner so that it can help businesses achieve efficiency in the financial recording process.